(untitled) (Praxis Educativa, 2021)
This research begins with the question: What is the notion of teaching competencies and under what experiences or sources are these competencies being built? The objective seeks to understand the concept of teaching competencies from the perceptions and meanings given by the teaching staff in their professional performance. The research is located within the interpretive paradigm. We work with a phenomenological theoretical perspective, from a hermeneutic methodological approach. Information is collected through in-depth interviews, focus groups, and participant observation. One of the results of the information collected leads us to understand the meaning that teachers give to teaching skills is related to the ability to transmit information, which is framed in a positivist paradigm. Given this, it is clear that the roles assigned to both teachers and students are not in accordance with current requirements.